Does retail food diversity in urban food environments influence consumer diets? - Chege, Christine G. Kiria; Wanyama, Rosina; Lundy, Mark M.; Nguru, Wilson; Jäger, Matthias (MDPI, 2021)
The food environment influences consumer diets in significant yet underexplored ways. In this study, we assess the way in which the Nairobi urban food environment—availability, accessibility, affordability, desirability, convenience and marketing—influences the dietary choices and quality of poor urban consumers, by combining market-level diversity scores (MLDS) with household and individual data collected from resource-poor (slum) neighbourhoods in Nairobi, Kenya. We find that urban-poor settings are characterized by a variety of food retail venues, including informal markets such as kiosks, mom-and-pop shops and tabletop vendors, as well as modern retail outlets such as supermarkets. Most of these food outlets predominantly sell unhealthy, highly-processed and energy-dense foods rather than nutritious foods such as vegetables, fruits and animal products. Our analyses show that supermarkets have the highest MLDS, yet they do not significantly influence the diets of resource-poor households. However, a high MLDS among informal retail outlets has a positive association with diet quality; conversely, open-air markets have a negative association. The nutritional status of urban-poor consumers can be improved by promoting the diversification of healthy, nutritious foods across traditional retail outlets and improving accessibility of the outlets to consumers.